Homeboy - Morgan, Seth (Vintage, 1998)
The first novel of an author who was a survivor of the the San Francisco street drug culture and a former convict. It aims to capture the underside of big-city life and pillory the prison system as it takes the reader on a nightmarish journey between criminality and justice.